Islamophobia in Karine Tuil’s The Age of Reinvention Novel - Ellita Permata Widjayanti (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
Islamophobia constitutes a negative action, attitude, and prejudice towards Islam as an ideology and against Muslims as followers of the ideology. It exists in any context and media including fictional works. This article discusses Islamophobia in an (English-translated) French novel entitled The Age of Reinvention written by Karine Tuil. The discussion focuses on how Islam and Muslims are represented in the novel and how the author uses some ironies to convey certain ideology. The author tends to be Islamophobic by describing Muslims as fatalist and immoral, and Islam as an uncivilized religion, barbaric, supportive of terrorism and irrational. Through the characters, narrations, and dialogues, the author also tends to have a sentiment on some issues related to Islam.